Alat Pendingin Dan Pemanas Portable Menggunakan Modul Termoelektrik Tegangan Input 6 Volt Dengan Tambahan Heat Pipe Sebagai Media Pemindah Panas - Hendra Abdul Aziz; Rahmat Iman Mainil; Azridjal Aziz (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Portable coolers and heaters use thermoelectric modules with an additional heat pipe as a heat transfer median. This research is to know the cooling temperature that can be achieved by the utilization of thermoelectric heat exhaust as heater with 6 volt input voltage. The effect of heat pipe usage on cooling and heating temperatures is also observed. In this study the use of heat pipe provides a better cooling effect where the temperature is lower than the test without heat pipes for 50 minutes. Achievement of cooling and heating chamber under non-heat-free heat pipe 23.41 oC and 32.36 oC, whereas by using heat pipe the achievement of cooling and heating chamber reaches 22.83 oC and 30.52 oC. Tests by using an additional heat pipe as a heat transfer achievement of cooling chamber and heating chamber become lower compared with testing without heat pipe.Keywords : Thermoelectric, Portable, Heat pipe, Input voltage, 6 volts.